Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T21:32:25+01:00
A)4x-3=3x+5
4x-3x=5+3
x=8

b)5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=5/8

c)3(x-1)=0
3x-3=0
3x=3 /:3
x=1

d)-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x=-5

e)-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-14-1
-10=-15 /:(-10)
x=15/10
x=1,5

f)4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5
6 4 6
2010-03-04T21:33:26+01:00
2.
a) 4x-3x=5+3
1x = 8 /: 1
x = 8
b) 5x+3x=7-2
8x=5 /:8
x = 0.625
c) 3x-3=0
3x=0+3
3x=3 /:3
x = 1
d) -6x+(-6) = 24
-6x = 24 - 6
-6x = 18 /:-6
x = -3
e) -7x+14=3x-1
-7x-3x = -1 -14
-10x = -15 /:-10
x = 1.5
f) 4x-4=6+6x
4x-6x = 6 + 4
-2x = 10 /: -2
x = -5
2 3 2
2010-03-04T21:46:24+01:00
4x-3=3x+5
4x-3x=5+3
x=8

5x+2=7-3x
5x+3x=7-2
8x=5/:8
x=5/8

3(x-1)=0
3x-3=0
3x=3/:3
x=1

-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/:(-6)
x=-5

-7x+14=3x-1
-7x-3x = -1 -14
-10x = -15 /:-10
x = 1.5

4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:(-2)
x=-5
2 3 2